2006
DOI: 10.1007/s00213-006-0560-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of pavlovian drug conditioned stimuli on in vivo dopamine transmission in the rat accumbens shell and core and in the prefrontal cortex

Abstract: The results show that drug CSs stimulate DA release in the shell and medial PFCX and specifically potentiate the primary stimulant drug effects on DA transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 60 publications
(63 reference statements)
5
57
0
Order By: Relevance
“…Although a specific role glutamate signaling in the shell vs. core in opiate seeking remains debatable, the shell-specific plasticity shown here is consistent with previous reports implicating a role for this region in opiate reward and relapse to drug seeking (19,(38)(39)(40)(41)(42)(43). It is worth noting, however, that reductions in NAc core A/N ratios due to up-regulation of NR2B-containing NMDAR currents have been reported following heroin self-administration in rats, and that this adaptation drives reinstatement of heroin seeking (24).…”
Section: Prefer Test Pre-testsupporting
confidence: 91%
“…Although a specific role glutamate signaling in the shell vs. core in opiate seeking remains debatable, the shell-specific plasticity shown here is consistent with previous reports implicating a role for this region in opiate reward and relapse to drug seeking (19,(38)(39)(40)(41)(42)(43). It is worth noting, however, that reductions in NAc core A/N ratios due to up-regulation of NR2B-containing NMDAR currents have been reported following heroin self-administration in rats, and that this adaptation drives reinstatement of heroin seeking (24).…”
Section: Prefer Test Pre-testsupporting
confidence: 91%
“…This viewpoint is also supported by animal studies showing that MD but not CUPS induce severe anhedonia in rats (Bai, Zhang, et al., 2014). MD and CUPS also exert dissimilar effects on the expression of D1, D2‐like receptors, and DAT in some of the mesocorticolimbic dopaminergic pathways (Bassareo, De Luca, & Di Chiara, 2007; Brenes & Fornaguera, 2008). In this study, we first demonstrated that different depressive behaviors of rats such as anhedonia, passive coping behavior, and exploratory interest may be related to divergent dopaminergic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pharmacological manipulations of the NAc that increase affective oro-facial responses to the taste of sweet solutions are specific to the dorsal shell subregion, a so called 'hedonic hotspot' (Pecina and Berridge, 2005;Pecina et al, 2006). Further, the shell region appears to be involved in processing the primary reinforcing effects of drugs of abuse (Bassareo et al, 2007;Ito et al, 2004). Electrophysiological and pharmacological studies of this region have shown that, generally, increases in motivated behavior for a given stimulus appear to be driven by decreased activity in the NAc shell (Carlezon and Wise, 1996).…”
Section: Role Of Dopamine and Other Neurotransmitters In Reward And Amentioning
confidence: 99%
“…Furthermore, dopamine function in the core subregion of the NAc has been implicated in mediating the association of natural reward-related stimuli (Day et al, 2007;Parkinson et al, 2002) and the proper behavioral responses to stimuli that predict cocaine (Di Chiara et al, 2004;Ito et al, 2000;Ito et al, 2004). In contrast, the shell appears to be more responsive to the primary reinforcing or motivational properties of drugs and natural rewards (Di Chiara et al, 2004;Kelley et al, 2002;Kelley and Swanson, 1997;Pecina and Berridge, 2005); however see (Bassareo et al, 2007;Cheer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%